8. Implementasi Pembelajaran Berbasis Perpustakaan Meningkatkan Minat Membaca Dan Hasil Belajar Siswa - ., Wariyono; darmawati, endamg (PGSD Universitas WR Supratman Surabaya, 2017)
Learning Indonesian in class IV-A SDI Al Akbar is still centered on the teacher as a source of learning and the student becomes the object of learning. Teachers are less able to develop resources and learning media in accordance with the characteristics of the material. This causes students to become passive. As a result of learning results Indonesian grade IV-A SDI Al Akbar is still low below the minimum standard criteria of completeness (KKM). It is necessary to solving the problem is with the library-based learning by implementing. The purpose of this study was to describe interest in reading, student learning outcomes, as well as the constraints faced by students and researchers at the time of learning by applying the Indonesian-based learning library. This type of research is classroom action research conducted by two cycles because it is based on indicators of achievement learning, remedial action is stopped if the student has reached KKM amounted to 85% of the total number of students in full, each cycle consisting of two meetings. Based on the research and analysis of data, obtained by the learning outcomes of students has increased by 37.50% in the percentage of completeness preliminary findings, 50.00% in the first cycle, and 87.50% in the second cycle.